The Effects of Crude Alkaloid Extracts of Convolutes Arvensis on Tumour Cell Lines and Their Potential For Toxicity: Efek Ekstrak Alkaloid Kasar dari Convolutes Arvensis pada Garis Sel Tumor dan Potensi Toksisitasnya - Hussein , Arwa Alaa (Academia Open, 2024)
General Background: Cancer remains a leading cause of mortality worldwide, and the search for effective treatments continues to intensify. Specific Background: Convolvulus arvensis has been traditionally used for medicinal purposes, but its potential as an anticancer agent is underexplored. Knowledge Gap: The cytotoxic and apoptotic mechanisms of crude alkaloids extracted from C. arvensis against specific cancer cell lines have not been fully characterized. Aims: This study investigates the antioxidant activity and cytotoxic effects of C. arvensis crude alkaloids on mouse liver cancer (HC) and human breast cancer (AMJ13) cell lines, focusing on apoptosis-related gene expression. Results: The antioxidant activity of C. arvensis was comparable to that of ascorbic acid, with inhibition rates of 92.01% at 500 µg/ml. Crude alkaloids demonstrated dose-dependent cytotoxicity, with a maximum inhibition rate of 82.65% in AMJ13 cells and 79.49% in HC cells at 500 µg/ml. Gene expression analysis revealed upregulation of caspase-9, indicating apoptosis via the intrinsic mitochondrial pathway. Novelty: This study is among the first to provide molecular evidence of C. arvensis-induced apoptosis through the intrinsic pathway, offering a novel insight into its anticancer potential. Implications: These findings suggest that C. arvensis alkaloids could be developed as a therapeutic option for cancer treatment, with future studies needed to isolate specific compounds and assess their in vivo efficacy. Highlights: C. arvensis alkaloids show antioxidant activity similar to ascorbic acid. Alkaloids inhibit liver and breast cancer cell growth dose-dependently. Apoptosis triggered via caspase-9 through the mitochondrial pathway. Keywords: Convolvulus arvensis, alkaloids, cancer, apoptosis, antioxidant